2022
DOI: 10.1007/s40620-022-01493-9
|View full text |Cite
|
Sign up to set email alerts
|

From KDIGO 2012 towards KDIGO 2021 in idiopathic membranous nephropathy guidelines: what has changed over the last 10 years?

Abstract: The recommendations in the Kidney Disease: Improving Global Outcomes (KDIGO) 2021 guidelines regarding Idiopathic Membranous Nephropathy (IMN) management include significant changes as compared to those published in 2012. According to the recent guidelines, a biopsy is not always needed for IMN diagnosis; since diagnosis can be allowed for by the detection of circulating antibodies against the M-type transmembrane phospholipase A2 receptor (anti-PLA2R). Moreover, alterations in anti-PLA2R concentrations, along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…As per the 2021 recommendations from KDIGO, rituximab (RTX) is advised as the initial treatment for moderate-risk patients with a normal eGFR and significant proteinuria (exceeding 3.5 g/day). For high-risk patients characterized by a decreased eGFR, cyclophosphamide is recommended as the first-line treatment [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As per the 2021 recommendations from KDIGO, rituximab (RTX) is advised as the initial treatment for moderate-risk patients with a normal eGFR and significant proteinuria (exceeding 3.5 g/day). For high-risk patients characterized by a decreased eGFR, cyclophosphamide is recommended as the first-line treatment [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent among these is the antibody directed against the M-type phospholipase A2 receptor (PLA2R), identified in 75 to 85% of patients with primary membranous nephropathy [ 5 , 6 ]. Recent discoveries include other target molecules, such as thrombospondin-type-1-domain-containing 7A (THSD7A), neural epidermal growth factor type 1 protein (NELL-1), semaphorin 3B (SEMA3B), superoxide dismutase 2 (SOD2), and aldose reductase (AR) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 The 2012 KDIGO Clinical Practice Guideline for Glomerulonephritis recommends rituximab or cyclophosphamide and alternate month glucocorticoids for 6 months, or CNI-based therapy for ≥6 months for patients with MN and at least one risk factor for disease progression. 18 One clinical study showed that CNIs increased the likelihood of partial or complete remission of proteinuria compared with no treatment (72–75% vs 22%) and that the remission rate at 12 months of treatment was comparable to and numerically higher than that of cyclophosphamide (71–89% for CNIs; 65–77% for cyclophosphamide). 19 In a retrospective study, tacrolimus induced remission of membranous nephropathy in 84% of patients.…”
Section: Discussionmentioning
confidence: 99%